ChemInform Abstract: Sugar‐Functionalized Carbon Nanotubes: Unique Properties and Interactions with Biological Species. Issue 11 (8th March 2013) - Anilkumar, Parambath; Tackett, Kenneth N., II; Lu, Fushen; Luo, Pengju G.; Gu, Lingrong; Anderson, Ankoma; Sun, Ya‐Ping
Abstract Review: 49 refs.